Stand up! : be an upstander and make a difference - Moss, Wendy (Wendy L.) (Magination Press, 2019)
Teaches kids how to be an upstander and make a difference in their sphere of influence. Includes practical advice, quizzes, and real-life examples of kids who have showed empathy for others, spread kindness, and dealt respectfully with conflicts.